REASONS WHY MEN WHO HAVE SEX WITH MEN VISIT ONE NON-GOVERNMENTAL ORGANIZATION IN BELGRADE - Bjekić, Milan (HEALTH CARE, 2024)
Introduction/Aim: The stigma surrounding men who have sex with men (MSM) and HIV/AIDS represents a significant barrier for the prevention, as well as for the treatment and prognosis of the disease. Non governmental organizations working with these vulnerable groups, besides providing various forms of support, also offer free testing for syphilis and HIV infection. The aim of this research is to determine the reasons for MSM individuals to visit a non-governmental Checkpoint center for the prevention of sexually transmitted infections (STIs), counseling, testing, and support, as well as profiling the motives for coming to the center. Methods: The study included 413 MSM individuals. All center users completed an anonymous questionnaire covering questions about basic demographic characteristics, reasons and motives for comming to the center, as well as an assessment of satisfaction with the services received. Users who came for laboratory diagnosis of syphilis and HIV underwent third-generation immunochromatographic rapid screening tests. Results: The average age of users was 30.6±8.44 years. Most center users were from Belgrade (85.7%) and employed (86%). Over 95% of users came to the Checkpoint center to be tested for HIV and syphilis, 12.1% of them came for pre-exposure prophylaxis (PrEP) for HIV, while a smaller percentage came for dermatological examination (6.5%) and psychological counseling (2.4%). Out of a total of 393 persons tested for HIV and syphilis, a positive HIV test was recorded in 10 (2.5%) users and syphilis in 25 (6.4%). The most common motives for coming to the center were the positive atmosphere and discretion provided to users (79.9%), availability of HIV and syphilis tests without a doctor’s referral (57.9%), absence of stigma and judgment in the center (54%), and flexible working hours (47.5%). Users rated their satisfaction with the services received at the center with an average mark of 4.97±0.12. Conclusion: Due to the stigmatization accompanying the MSM population and individuals living with HIV infection, non-governmental organizations working with these vulnerable groups in collaboration with the public health sector play a significant role in controlling the spread and prevention of STIs and HIV. The availability of centers, friendly atmosphere, discretion, and absence of stigma and discrimination are reasons why members of the MSM population willingly visit them.